Cucumber susceptibility to simulated soil residues of clomazone - Gajić Umiljendić, Jelena; Đorđević, Tijana; Šantrić, Ljiljana; Sarić-Krsmanović, Marija; Radivojevic, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
A laboratory bioassay was conducted to investigate the susceptibility of cucumber to the residual activity of clomazone in loamy and sandy soils. The effects of three different levels of soil moisture (20, 50 and 70% field capacity - FC) was also examined. Clomazone was applied in concentration series of 0.047-6 mg a.i./kg soil. Plants grew for 21 days, upon which period physiological parameters (content of carotenoids, chlorophyll a and chlorophyll b) were measured. Clomazone caused leaf bleaching and reduction in pigments content in cucumber leaves in both types of soil at all levels of soil moisture, and the degree of change depended on application rates. Inhibition was higher in plants grown in the sandy soil, while the least sensitive were cucumber plants grown in both types of soil with 20% FC. The findings in this study showed moderate cucumber susceptibility to clomazone residues in loamy and sandy soils.